2021
DOI: 10.37965/jait.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mechanical Adhesion Climbing Robot Design for Wind Tower Inspection

Abstract: Mmaintenance of wind turbine farms is a huge task, with associated significant risks and potential hazard to the safety and wellbeing of people who are responsible for carrying the tower inspection tasks. Periodic inspections are required for wind turbine tower to ensure that the wind turbines are in full working order, with no signs of potential failure. Therefore, the development of an automated wind tower inspection system has been very crucial for the overall performance of the renewable wind power generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…WBC segmentation is carried out using the MASK-RCNN network for blood images through the semantic segmentation process; meanwhile, these WBCs relate to positive classes and their pixel relates to negative, which is shown in Figure 4 ; for the input images, the initial process to train the model, ResNet [ 1 , 24 ] was scaled to 224 ∗ 224 to maintain stability and to scale the output of the network. Later, for the ground truth, sample labels were applied to each pixel by making them to the chosen label/class.…”
Section: Resources and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…WBC segmentation is carried out using the MASK-RCNN network for blood images through the semantic segmentation process; meanwhile, these WBCs relate to positive classes and their pixel relates to negative, which is shown in Figure 4 ; for the input images, the initial process to train the model, ResNet [ 1 , 24 ] was scaled to 224 ∗ 224 to maintain stability and to scale the output of the network. Later, for the ground truth, sample labels were applied to each pixel by making them to the chosen label/class.…”
Section: Resources and Methodsmentioning
confidence: 99%
“…From the above literature, it is found that the existing models suffer from hyperparameters tuning [ 1 , 24 26 ], gradient vanishing [ 27 , 28 ], and overfitting [ 29 31 ] problems. Therefore, an efficient model is required that can overcome these issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…e experimental results demonstrated that the combined approach of SVM and IPSO had higher accuracy. However, the majority of the existing models suffer from overfitting [23][24][25], poor convergence speed [26][27][28], and vanishing gradient problems [29][30][31].…”
Section: Literature Surveymentioning
confidence: 99%
“…The implications of substantial quantities of improperly classified data in medical image classification are catastrophic, and the objective of proposing a medical diagnosis tool is wrecked. In addition to efficiency, additional parameters such as F1 score [ 25 , 26 ], area under the curve (AUC) [ 27 , 28 ], sensitivity [ 29 , 30 ], and specificity [ 31 33 ] are vital in analyzing various approaches. A random sample of cell images infected/not infected with malaria is shown in Figure 1 .…”
Section: Related Workmentioning
confidence: 99%